Palbociclib synergizes with BRAF and MEK inhibitors in treatment naïve melanoma but not after the development of BRAF inhibitor resistance. Issue 10 (3rd January 2018) - Martin, Claire A.; Cullinane, Carleen; Kirby, Laura; Abuhammad, Shatha; Lelliott, Emily J.; Waldeck, Kelly; Young, Richard J.; Brajanovski, Natalie; Cameron, Donald P.; Walker, Rachael; Sanij, Elaine; Poortinga, Gretchen; et al.
Abstract : Increased CDK4 activity occurs in the majority of melanomas and CDK4/6 inhibitors in combination with BRAF and MEK inhibitors are currently in clinical trials for the treatment of melanoma. We hypothesize that the timing of the addition of CDK4/6 inhibitors to the current BRAF and MEK inhibitor regime will impact on the efficacy of this triplet drug combination. The efficacy of BRAF, MEK and CDK4/6 inhibitors as single agents and in combination was assessed in human BRAF mutant cell lines that were treatment naïve, BRAF inhibitor tolerant or had acquired resistance to BRAF inhibitors. Xenograft studies were then performed to test the in vivo efficacy of the BRAF and CDK4/6 inhibitor combination. Melanoma cells that had developed early reversible tolerance or acquired resistance to BRAF inhibition remained sensitive to palbociclib. In drug‐tolerant cells, the efficacy of the combination of palbociclib with BRAF and/or MEK inhibitors was equivalent to single agent palbociclib. Similarly, acquired BRAF inhibitor resistance cells lost efficacy to the palbociclib and BRAF combination. In contrast, upfront treatment of melanoma cells with palbociclib in combination with BRAF and/or MEK inhibitors induced either cell death or senescence and was superior to a BRAF plus MEK inhibitor combination. In vivo palbociclib plus BRAF inhibitor induced rapid and sustained tumor regression without the development of therapy resistance. In summary, upfront dual targeting of CDK4/6 and mutant BRAF signaling enables tumor cells to evade resistance to monotherapy and is required for robust and sustained tumor regression. Melanoma patients whose tumors have acquired resistance to BRAF inhibition are less likely to have favorable responses to subsequent treatment with the triplet combination of BRAF, MEK and CDK4/6 inhibitors. Abstract : What's new? Cutaneous melanoma is marked by high incidence of BRAF mutations and cyclin‐dependent kinase 4 (CDK4) deregulation. Thus, the combination of CDK4 inhibition with BRAF and MEK inhibition is a promising strategy toward improving melanoma survival. Here, addition of the CDK4/6 inhibitor palbociclib upfront with BRAF and MEK inhibitors blocked the development of drug resistance and produced robust, durable responses in BRAF mutant melanoma cells. The synergistic effects were lost when palbociclib was started after melanoma cells became resistant to BRAF inhibition. The findings provide a rationale for upfront first‐line treatment with CDK4/6, BRAF, and MEK inhibitors in melanoma patients.